2013
DOI: 10.1142/s0219519413500668
|View full text |Cite
|
Sign up to set email alerts
|

Homotopy Simulation of Two-Phase Thermo-Hemodynamic Filtration in a High Permeability Blood Purification Device

Abstract: A two-phase thermo-hydrodynamic model is presented for transport in the vertical chamber of a porous media blood filtration device. A non-Darcy drag force formulation was employed. The MarbleÀDrew fluidÀparticle suspension model was used to simulate the plasma phase and the suspension (erythrocyte) particle phase. The non-dimensional transport equations were solved using a semi-computational procedure known as the homotopy analysis method (HAM). With the judicious use of the auxiliary parameter }, HAM affords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Hayat et al [49] examined the non-Fourier thermal convection of carbon nanotube fluids over a curved stretching surface. Other applications of HAM in biological fluid dynamics and nanoscale transport include [50][51][52]. To extract the solutions of Equations (7)-(9) subject to the boundary conditions (10) using HAM, we have considered initial guesses f 0 , θ 0 and φ 0 of f , θ and φ in the following form:…”
Section: Solution Using Homotopy Analysis Methodsmentioning
confidence: 99%
“…Hayat et al [49] examined the non-Fourier thermal convection of carbon nanotube fluids over a curved stretching surface. Other applications of HAM in biological fluid dynamics and nanoscale transport include [50][51][52]. To extract the solutions of Equations (7)-(9) subject to the boundary conditions (10) using HAM, we have considered initial guesses f 0 , θ 0 and φ 0 of f , θ and φ in the following form:…”
Section: Solution Using Homotopy Analysis Methodsmentioning
confidence: 99%
“…The current study has demonstrated the excellent accuracy and stability characteristics of the modified cubic B-spine differential quadrature method (MCB-DQM) in numerical simulations of interfacial two-fluid (dusty-micropolar) duct flows. However, heat transfer and electromagnetic effects [54], [55] have been neglected. These may be considered in future studies and are also of relevance in biomedical and materials processing systems.…”
Section: Discussionmentioning
confidence: 99%
“…Vasu and Ray (2019) applied HAM to discuss the non-similarity solution for the flow of Carreau nanofluid past vertical plate with Cattaneo–Christov heat flux model. Other applications in biological fluid dynamics and nanoscale transport include (Bég et al , 2012; Bég, et al , 2013; Tripathi and Bég, 2015; Srinivas and Bég, 2018). To extract the solutions of the equations (15) to (18) subjected to the boundary conditions in equation (19) using HAM, we take the initial guesses f 0 , θ 0 , ϕ 0 and χ 0 of f , θ , ϕ and χ in the following form: …”
Section: Homotopy Analysis Methodsmentioning
confidence: 99%